Climate and Labor Flexibility Again Covid-19 - Cruz García Lirios (Universitas Negeri Makassar, 2021)
Objective. Gross mode, the work climate has been studied as an area inherent in leadership. In the case of the one that is distinguished by its communication and vertical motivation, the work environment has been addressed as a determinant of flexibility in terms of conditions, salaries and benefits. In this regard, the objective of this paper has been to explore the dimensions of climate and labor flexibility in order to establish the dependency relationships between its indicators. Methodology. A non-experimental, cross-sectional and correlational study was carried out with a non-probabilistic sample selection of 300 employees from central Mexico. Results and conclusions. The labor climate determines the flexibility, although the most recent literature warns that rather the climate mediates the relationship between the flexibility policies on staff turnover, the informal salary and the absence of benefits. Research lines are recommended concerning the incidence of leadership styles in the variables in question.